Medical professionalism education: a systematic review of interventions, outcomes, and sustainability - Sadeq, Asil; Guraya, Shaista S.; Fahey, Brian; Clarke, Eric; Bensaaud, Abdelsalam; Doyle, Frank; Kearney, Grainne P.; Gough, Fionnuala; Harbinson, Mark; Guraya, Salman Yousuf; Harkin, Denis W. (Frontiers in Medicine, 2025)
IntroductionMedical professionalism (MP) is a vital competency in undergraduate medical students as it enhances the quality and safety of patient care as it includes professional values, attitudes and professional behaviours (PB). However, medical institutes are uncertain about how optimally it can be learnt and assessed. This review aims to systematically provide a summary of evidence from systematic reviews reporting MP educational interventions, their outcomes and sustainability to foster PB.MethodsEight major databases (CINAHL, EMBASE, ERIC, Health business, Medline, OVID, PsycINFO, SCOPUS and Web of Science) and grey literature were systematically searched from database inception to June 2024. The inclusion criteria were (1) systematic review studies (2) of educational interventions of any type; (3) targeting any aspect of MP; (4) provided to undergraduate medical students; and (5) with no restrictions on comparator group or outcomes assessed. A qualitative narrative summary of included reviews was conducted as all included reviews did not conduct quantitative nor meta-analysis of results but rather a qualitative summary. Methodological quality of included reviews was assessed using A MeaSurement Tool to Assess systematic Reviews (AMSTAR) 2 tool.ResultsThe search identified 397 references for eligibility screening. Ultimately, eight systematic reviews were deemed eligible for inclusion. The majority of these reviews have reported a successful improvement in various aspects of MP (i.e., MP as a whole, empathy and compassion) through teaching and exposure to hidden curriculum. The included studies displayed significant methodological heterogeneity, with varying study designs and assessment methodologies to professional outcomes. A gap remains in reporting the sustainable effect on professionalism traits and on a standardised approach to MP teaching.ConclusionThis review suggests that more interventions are needed in this area with a focus on methodological quality and teaching methods in a multicultural context to support PB and professional identity formation.Clinical trial registrationPROSPERO [CRD42024495689].